Current block motions and strain accumulation on active faults in the Caribbean. Issue 5 (19th May 2015) - Symithe, S.; Calais, E.; de Chabalier, J. B.; Robertson, R.; Higgins, M.
Abstract The Caribbean plate and its boundaries with north and south America, marked by subduction and large intra‐arc strike‐slip faults, are a natural laboratory for the study of strain partitioning and interseismic plate coupling in relation to large earthquakes. Here we use most of the available campaign and continuous GPS measurements in the Caribbean to derive a regional velocity field expressed in a consistent reference frame. We use this velocity field as input to a kinematic model where surface velocities results from the rotation of rigid blocks bounded by locked faults accumulating interseismic strain, while allowing for partial locking along the Lesser Antilles, Puerto Rico, and Hispaniola subduction. We test various block geometries, guided by previous regional kinematic models and geological information on active faults. Our findings refine a number of previously established results, in particular slip rates on the strike‐slip faults systems bounding the Caribbean plate to the north and south, and the kinematics of the Gonave microplate. Our much‐improved GPS velocity field in the Lesser Antilles compared to previous studies does not require the existence of a distinct Northern Lesser Antilles block and excludes more than 3 mm/yr of strain accumulation on the Lesser Antilles‐Puerto Rico subduction plate interface, which appears essentially uncoupled. The transition from a coupled to an uncoupled subduction coincides with a transition in the long‐term geological behavior of the Caribbean plate margin from compressional (Hispaniola) to extensional (Puerto Rico and Lesser Antilles), a characteristics shared with several other subduction systems.